Objectives and Obligations of Dialogue of Religions - Masson, J. (Journal of Dharma, 1975)
Before becoming and action, dialogue is a contact; even before becoming a contact and in order to be a contact, dialogue is a spirit. Only then do we come to the practical event, dialogal action. As our old authors have often remarked, "we act according to what we are." Before having an effect on someone else, we must thus be ourselves; before giving out things or ideas or even giving our love we must be ourselves. Moreover, even in meeting with someone, it is not the place where one happens to be, the office one is performing at the words one says, which constitute the essential; but in depth what one is, as a man, as a Christian. Before starting a dialogue, before even thinking of dialogue, one should evaluate and question whether he may be too frivolous, whether he has the necessary weight of humanness and of holiness. This is the first practical aspect.